Pengembangan Media E-Learning Berbasis Learning Management System (LMS) Moodle pada Materi Trigonometri di Kelas X SMAN 1 Lingsar - Abdul Haris Munandar; Amrullah Amrullah; Junaidi Junaidi; Arjudin Arjudin (Griya Journal of Mathematics Education and Application, 2022)
This study aims to produce and determine the feasibility of e-learning based Learning Management System (LMS) Moodle in class X trigonometry. This type of research is development research using the ADDIE model, namely Analysis, Design, Development, Implementation, and Evaluation. Data was collected through validation of e-learning by validators and student response questionnaires. Development media in research This was validated by material experts, media experts, and tested on class X students of SMAN 1 Lingsar, West Lombok, NTB. The test subjects in the development of this media were 34 students of class X IPA 1 who were selected using purposive sampling technique. The results showed that at the validation stage by material experts and media experts, the validity results were 90.67% and 90.00% with the media category "Very Eligible". Meanwhile, at the trial stage, the response of students to e-learning obtained an average result of 87.23%, namely in the "Very Good" category. Thus, it can be concluded that e-learning is very suitable for use by class X students of SMAN 1 Lingsar, especially in trigonometry material.